Classification, diagnosis, and management of orbital venous-lymphatic malformations: Current state-of-the-art - Yueh-Ju Tsai; Angel Chao; Yen-Chang Chu; An-Ning Chao (Taiwan Journal of Ophthalmology)
Orbital venous-lymphatic malformations (VLMs) are complex vascular anomalies that pose significant challenges to ophthalmologists due to their diverse clinical manifestations and the difficulties inherent in their therapeutic management, particularly given their proximity to critical orbital structures. This narrative review synthesizes the current knowledge on the classification, pathology, molecular mechanisms, imaging characteristics, and therapeutic strategies for VLMs. Historically misclassified as orbital lymphangiomas, VLMs are now recognized as complex malformations comprising interconnected venous and lymphatic components, with the potential for significant complications, including proptosis, visual impairment, and esthetic disturbances. Recent molecular insights have revealed critical pathogenetic mechanisms, particularly mutations in the PIK3CA gene that activate the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin transduction network, alongside the upregulation of vascular endothelial growth factor (VEGF)-mediated signaling. These aberrations not only illuminate the disease etiology but also present promising therapeutic targets. Contemporary management strategies emphasize a multidisciplinary approach, with sclerotherapy emerging as a particularly promising intervention. Sclerosing agents such as bleomycin and pingyangmycin typically yield effective treatment outcomes with relatively favorable safety profiles. Surgical excision is reserved for accessible lesions but often requires adjunctive therapies due to the infiltrative nature of VLMs. Emerging treatments targeting molecular pathways, including PI3K inhibitors and anti-VEGF therapies, show promise in refractory cases. As our understanding deepens, clinicians can now offer more personalized interventions that consider factors such as lesion location, extent, architecture, and hemodynamic characteristics, thereby minimizing morbidity and optimizing clinical and aesthetic outcomes.